THE IMPACT OF ENVIRONMENTAL PROBLEMS ON HUMAN HEALTH - Samadova Kh. S. (American Journals, 2024)
In the modern world, environmental protection measures are coming to the fore. The consequences of insufficient attention to the problem related to the environmental situation can be catastrophic for the entire planet. It is not only about the well-being of humanity, but also its survival. It is especially alarming that the deterioration of the natural environment may be irreversible.
Keywords: Ecology, nature, toxic gases, radioactive substances, industrial waste.